Aortic occlusion in systemic lupus erythematosus associated with antiphospholipid antibodies. Issue 8 (August 1987) - Drew, P; Asherson, R A; Zuk, R J; Goodwin, F J; Hughes, G R
Abstract : The patient, a Caucasian woman of 22 years, developed malignant hypertension at the age of 16 years. An abdominal bruit was found on routine examination. She had two spontaneous abortions and systemic lupus erythematosus was diagnosed at age 21 years. She was found to have a persistently low positive VDRL and antibodies to mitochondria were also present on repeated examinations, to a titre of 1/160. Because of angiographic findings, demonstrating an occlusion of the aorta, an endarterectomy of the descending thoracic and upper abdominal aorta was performed. This showed mainly intimal thickening and the presence of thrombus. She then had four further spontaneous abortions (with good blood pressure control). The lupus anticoagulant and antibodies to cardiolipin were found to be positive at this time.